Use of contemporary technologies and new materials in undergraduate Endodontics teaching - Jiménez-Sánchez, Mari-Carmen (J Clin Exp Dent, 2021)
BACKGROUND: This study aims to analyze the use of contemporary technologies and materials in undergraduate endodontic teaching in Spain. MATERIAL AND METHODS: The survey was sent to the undergraduate endodontic programme leads in the 23 Spanish dental schools. The survey asked about the use of magnification, ultrasonic devices, electronic apex locator, rotary instruments, root-filling techniques, and bioceramic cements in the teaching of endodontics. RESULTS: The response rate was 91%, and the final number of schools included in the study was twenty. Only two schools (10%) used magnification (loupes or operative microscope). Five schools (25%) used ultrasonic devices to prepare the access cavity, and four (20%) to activate the irrigation solution. In 14 dental schools (70%) no type of ultrasonic instrument was used. Electronic apex locators in working length determination was used in 19 schools (95%). All schools used rotary instrumentation in the teaching of endodontics, and 45% of schools used reciprocating instruments. Five schools (25%) used warm vertical compaction technique, four (20%) single cone gutta-percha technique, and four (20%) thermoplastic injection techniques. No school used carrier-based gutta-percha. Bioceramic cements were used in 19 of the schools (95%). CONCLUSIONS: Spanish dental schools have incorporated some of the new endodontic technologies and materials, including the electronic apex locator, rotary instruments, and the new bioceramic cements; however, the modern root filling techniques, magnification, and ultrasonic instruments are not yet used in most dental schools. Key words:Bioceramic materials, dental schools, endodontic curriculum, magnification, online survey, rotary instrumentation, ultrasonic devices.